Structural and functional characterization of the cardiac mitochondria-associated reticular membranes in the ob/ob mouse model - Hala Guedouari; Maya Dia; Juliette Geoffray; Camille Brun; Florentin Moulin; Lucas Givre; Lucid Belmudes; Christelle Leon; Stephanie Chanon; Jingwei Ji-Cao; Christophe Chouabe; Sylvie Ducreux; et al. (Journal of Molecular and Cellular Cardiology Plus)
Type 2 diabetes (T2D) and obesity strongly lead to diabetic cardiomyopathy (DCM). The involvement of mitochondria-associated reticular membranes (MAMs), a signaling hub in the cardiomyocyte, starts to be demonstrated in T2D-related metabolic disorders. We recently discovered a cardiac MAM Ca2+ uncoupling in a high-fat high-sucrose diet (HFHSD)-induced mouse model of DCM. To better determine the role of MAMs in the progression of DCM, we here aimed to characterize the proteomic composition and function of the cardiac MAMs of another obesogenic T2D mouse model, the leptin-deficient ob/ob mouse.12-week old male C57Bl6-N ob/ob mice displayed strain rate dysfunction and concentric remodeling, while no change was observed in fractional shortening or diastolic function. Increased lipid deposition but no fibrosis was measured in the ob/ob heart compared to WT. Electron microscopy analysis revealed that cardiac MAM length and width were similar between both groups. A trend towards an increased MAM protein content was measured in the ob/ob heart. MAM proteome analyses showed mainly increased processes in ob/ob hearts: cellular response to stress, lipid metabolism, ion transport and membrane organization. Functionally, MAM-driven Ca2+ fluxes were unchanged but hypoxic stress induced a cell death increase in the ob/ob cardiomyocyte. Mitochondrial respiration, cardiomyocyte shortening, ATP and ROS content were similar between groups.To conclude, at that age, while being strongly hyperglycemic and insulin-resistant, the ob/ob mouse model rather displays a modest DCM without strong changes in MAMs: preserved structural and functional MAM Ca2+ coupling but increased response to stress.